AB0086 BCP AND CPPD CRYSTALS INFLUENCE THE CHONDROCYTE PHENOTYPE IN DIFFERENT WAYS. (June 2019) - Kornak, Uwe; Meyer, Franziska; Bollmann, Miriam; Bertrand, Jessica
Abstract : Background: Calcification of cartilage with BCP crystals is a common finding during osteoarthritis (OA) and is directly linked to the severity of the disease and hypertrophic differentiation of chondrocytes. In some OA cartilage samples calcium pyrophosphate dihydrate (CPPD) crystals can be found. The mechanism underlying the formation of the CPPD crystals and their effects on the chondrocytes are not completely understood. Objectives: The aim of this study was to evaluate the effect of CPPD compared to BCP crystals on the chondrocyte phenotype in OA cartilage. Methods: Cartilage samples of patients with chondrocalcinosis were used and compared with samples of severe OA patients without chondrocalcinosis and healthy cartilage samples served as control. Radiological presence of chondrocalcinosis was evaluated using standard X-ray pictures, as well as macroscopically inspection. The cartilage samples were stained using von Kossa/Safranin-orange staining. These stainings were used for OA severity scoring using the Chambers-Score. Chondrocyte differentiation markers were evaluated using Collagen 2 and X, as well as Sox9 and aggrecan as markers for chondrocyte hypertrophic differentiation in immunohistochemistry and qRT-PCR. TUNEL staining was performed to investigate cell death. In vivo results were validated using qRT-PCR for the expression of the respective genes after stimulation of C28 chondrocytes with CPPD and BCP crystals. Results: Radiologically detectable cartilage calcifications were evident in chondrocalcinosis patients, but absent in OA patients without chondrocalcinosis. Chondrocalcinosis cartilage exhibited an increased collagen 10 expression compared to healthy cartilage, as well as to severe OA cartilage containing BCP calcification. Interestingly, aggrecan and collagen 2 were not reduced in chondrocalcinosis cartilage, but markedly reduced in OA cartilage. TUNEL positive cells were significantly increased in CPPD cartilage compared to OA cartilage, although the histological OA severity was lower. qRT-PCR indicated no relevant influence of CPPD crystals on hypertrophic marker genes, whereas BCP crystals significantly induced hypertrophic differentiation. Conclusion: BCP and CPPD crystals seem to trigger differential effects on the chondrocyte phenotype. BCP crystals induce hypertrophic differentiation, which is not induced by CPPD crystals. Disclosure of Interests: None declared